A case of aortoduodenal fistula caused by IgG4-related periaortitis - Oka, Hideki; Sumitomo, Shuji; Shimizu, Hayato; Kanamori, Maki; Yamashita, Daisuke; Nishioka, Hiroaki; Ohmura, Koichiro (Modern rheumatology case reports, 2023)
An 86-year-old man who underwent endovascular aortic repair for impending rupture of an abdominal aortic aneurysm a year ago presented to our hospital because of fatigue and black stools. Multiple bacterial specimens were detected in blood cultures, and computed tomography following oral administration of gastrografin demonstrated gastrografin in the abdominal aorta. The diagnosis of aortic duodenal fistula was confirmed and emergency abdominal aortic replacement was performed. The pathological findings of the aorta included a large number of immunoglobulin G4 (IgG4)-positive plasma cells infiltrating all layers of the aortic wall, with particularly marked thickening of the adventitia. The serum IgG4 level was 241 mg/dl and IgG4-related periaortitis was diagnosed. Aortoduodenal fistula is a rare but fatal complication of IgG4-related periaortitis. Patients should be followed carefully after endovascular aortic repair for inflammatory abdominal aortic aneurysms.